Reviving Islamic Education: : Ibn Khaldun's Influence on Contemporary Education - Azka, Sofiyyudin; Bakar, M. Yunus Abu (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2023)
The purpose of this article is to reveal Ibn Khaldun's views on education, which indirectly provide an overview of the Islamic education system that he considered ideal. In addition, this study will also try to assess the extent to which his thoughts influence the development of Islamic education in Indonesia today. The method used in this article is a qualitative descriptive analysis, which involves a literature study of previous research documents and texts. The results of the analysis show that Ibn Khaldun's thoughts on the Islamic education system have a significant impact on the development of Islamic education today. This can be seen in his views on the purpose of education, educational curriculum, classification of knowledge, methods of acquiring knowledge, learning methods, education system, educators and learners, educational environment, and its implications for contemporary Islamic education. [Tujuan dari artikel ini adalah untuk mengungkapkan pandangan Ibnu Khaldun tentang pendidikan, yang secara tidak langsung memberikan gambaran tentang sistem pendidikan Islam yang dianggapnya ideal. Selain itu, penelitian ini juga akan mencoba menilai sejauh mana pemikirannya memengaruhi perkembangan pendidikan Islam di Indonesia saat ini. Metode yang digunakan dalam artikel ini adalah analisis deskriptif kualitatif, yang melibatkan studi literatur terhadap dokumen dan teks-teks penelitian sebelumnya. Hasil analisis menunjukkan bahwa pemikiran Ibn Khaldun tentang sistem pendidikan Islam memiliki dampak yang signifikan terhadap perkembangan pendidikan Islam saat ini. Hal ini terlihat dalam pandangannya mengenai tujuan pendidikan, kurikulum pendidikan, klasifikasi ilmu, metode perolehan ilmu, metode pembelajaran, sistem pendidikan, pendidik dan peserta didik, lingkungan pendidikan, dan implikasinya terhadap pendidikan Islam kontemporer.]